A multilinguistic analysis of spelling among children with cochlear implants. (12th September 2018) - Quick, Nancy; Harrison, Melody; Erickson, Karen
Abstract: This study examines the spelling of nine elementary school children with cochlear implants (CIs) who use spoken language, and compares their performance with children who have typical hearing and children who are hard of hearing (HH). Compared to children with typical hearing, children with CIs did not produce a significantly different percentage of misspelled words ( p = 0.431, d = 0.38), but their spelling errors comprised significantly lower percentages of homophone substitutions ( p = 0.019, r = 0.61) and legal vowel errors ( p = 0.011, r = 0.61). Children with CIs and children who are HH did not produce a significantly different percentage of misspelled words ( p = 0.521, d = 0.31) or a significantly different distribution of categorical spelling errors. Results suggest that children with CIs utilize similar linguistic strategies as their peers who are HH but different strategies than peers with typical hearing when attempting to spell unfamiliar words.